Do Financial Statements Still Matter in the Tech Era? A Systematic Literature Review on the Usefulness of Accounting Information in High Volatility Firms - Ashar, Muhammad; Amaliah, Wafiq Azizah Reski; Darmawati, Darmawati; Syarifuddin, Syarifuddin (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study examines the evolution and relevance of accounting information in supporting decision making within technology sector firms characterized by high market volatility over the past decade. Adopting a systematic literature review (SLR) approach combined with bibliometric analysis, the study identifies key indicators discussed in the literature, including traditional GAAP based measures and non-financial metrics such as digital disclosures and intangible assets. The findings indicate that while traditional financial statements remain foundational, growing challenges arise from rapid market dynamics and global economic uncertainty, thereby driving the incorporation of non-financial data and digital technologies to enhance information relevance. These insights provide strategic implications for academics, practitioners, and policymakers in enriching the use of accounting information to support more accurate and adaptive decision-making in the digital era and volatile markets.